1.(n-2)(3n+7)+2n(2n+3)

factor each expression fully:

2. 4xsquared-25

- During exercise the body cools itself by sweating. sweating in response to an elevated body temperat... 11 months ago
- Surveys show that people who use calorie information to decide which foods to eat consume on average... 11 months ago
- A(n) _____ competitor provides a product or service that a consumer might buy instead of yours even... 11 months ago
- Tell us about a mistake you've made in your past and what you learned from that mistake. fire fighte... 11 months ago
- You work in an important and visible position in government. your decision is to choose between two... 11 months ago

- Matt (180lb male) goes to a party and is served beer in a 16 oz red plastic cup. he has 3 cups of be... 611 Views 11 months ago
- what other Chinese tradition involve bells?compare and contrast these tradition with Filipino tradit... 438 Views 1 year ago
- It is a good idea to learn about a food supplier's warehouse practices. The best way to gather the i... 386 Views 1 year ago
- Discuss FOUR contributory factors that lead to poverty in your community 381 Views 1 year ago
- What does Mark Twain satirize in this excerpt from "The £1,000,000 Bank-Note"? It was a lovely di... 333 Views 1 year ago

- mphogetrude 5.00
- Zina07 5.00
- Trevea 5.00

## Answers

## jbaby493

1.(n-2)(3n+7)+2n(2n+3)

We'll start with (n-2)(3n+7)

Use the FOIL method to simplify: First, Outside, Inside, Last.

Multiply the first numbers of each bracket (n and 3n), the outside numbers (n and 7), the inside numbers (-2 and 3n) and the last numbers (-2 and 7)

F= 3n×n= 3n²

O= n×7= 7n

I= -2×3n= -6n

L= -2×7= -14

Add them together, you get 3n² + n -14.

The second part is 2n(2n+3)

Multiply both numbers inside the bracket by 2n

2n×2n= 4n²

3×2n= 6n

Add these terms with the previous ones

7n² + 7n -14

Because they all have a common factor of 7, we can represent the equation as

7(n² + n -2)

2. 4x²-25

To factor this, we convert it into two expressions that we multiply together (like converting -9 into 3×-3)

2x × 2x= 4x²

5 × -5= -25

The answer is (2x+5)(2x-5)

## lyssie11234

[latex]1.\\(n-2)(3n+7)+2n(2n+3)\\\\=n\cdot3n+n\cdot7-2\cdot3n-2\cdot7+2n\cdot2n+2n\cdot3\\\\=3n^2+7n-6n-14+4n^2+6n\\\\=7n^2+7n-14[/latex]

==============================================================

[latex]2.\\4x^2-25=(2x)^2-5^2=(2x-5)(2x+5)[/latex]